Reformulation of Law Decision Bias on Restitution Payments in Sexual Violence Crimes (Comparison of Indonesia and The Netherlands) - Panusunan, Panusunan; Widyawati, Anis; Sulistianingsih, Dewi; Nababan, R. Kemala (Journal of Law and Legal Reform, 2025)
Sexual violence is an increasingly prevalent crime in Indonesia. Article 16 of Law Number 12 of 2022 on Criminal Acts of Sexual Violence states that, in addition to imprisonment, fines, or other criminal penalties as outlined in the Law, the judge is required to determine the amount of restitution for criminal acts of sexual violence that carry a sentence of four years in prison or more. One form of compensation available to victims of the criminal acts of sexual violence is restitution payments made by the defendant. However, many Panels of Judges still deny cases of the criminal acts of sexual violence restitution, particularly in verdicts where the defendant faces a four-year sentence or more. Several reasons explain why judges do not determine restitution payments by the defendant to the victim: the first is bias regarding the amount of compensation for victims in the judge’s decision; the second is that the request for payment restitution must be formally submitted; and the third concerns how to reformulate the determination of restitution in sexual violence cases (a comparison of Indonesia and the Netherlands).